2021
DOI: 10.3389/fnagi.2020.607445
|View full text |Cite
|
Sign up to set email alerts
|

Age-Associated Differences of Modules and Hubs in Brain Functional Networks

Abstract: Healthy aging is usually accompanied by changes in the functional modular organization of the human brain, which may result in the decline of cognition and underlying brain dysfunction. However, the relationship between age-related brain functional modular structure differences and cognition remain debatable. In this study, we investigated the age-associated differences of modules and hubs from young, middle and old age groups, using resting-state fMRI data from a large cross-sectional adulthood sample. We fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 88 publications
3
16
0
Order By: Relevance
“…In addition, no differences are found in α for individuals diagnosed with diabetes compared to healthy individuals (Figure S11) or for individuals diagnosed with bipolar disorder or depression compared to healthy individuals (Figure S12). While previous studies based on fMRI found modularity to be sensitive to age and disease, α is a coarse modularity proxy that, like the total number of modules across the brain, has been found to be fairly constant with respect to age and disease [33,34]. This result is consistent with our hypothesis that percolation is a necessary condition for brain function, rather than a parameter that tunes performance.…”
Section: 3supporting
confidence: 89%
“…In addition, no differences are found in α for individuals diagnosed with diabetes compared to healthy individuals (Figure S11) or for individuals diagnosed with bipolar disorder or depression compared to healthy individuals (Figure S12). While previous studies based on fMRI found modularity to be sensitive to age and disease, α is a coarse modularity proxy that, like the total number of modules across the brain, has been found to be fairly constant with respect to age and disease [33,34]. This result is consistent with our hypothesis that percolation is a necessary condition for brain function, rather than a parameter that tunes performance.…”
Section: 3supporting
confidence: 89%
“…For one, brain maturation processes from middle age to old age may play a role in the reduced prevalence of hallucinations in older adults. 23,24 For example, there is structural re-organisation of brain networks from middle adulthood to old age 25 that potentially results in weakened functional segregation and integration, 26 which may reduce the prevalence of hallucinations in older adults. 27 From a psychosocial perspective, research suggests that older adulthood is associated with the development of a number of skills that may reduce risk of hallucinations or their psychopathologic effects.…”
Section: Discussionmentioning
confidence: 99%
“…For each category, we selected a variety of widely used module detection methods to generate different network partition results to evaluate the influence of module detection algorithm on reliability. To ensure the quality of network partitions, we only kept top 10% strongest positive connections to ensure the sparsity of FC networks ( Wen et al, 2019 ; Zhang et al, 2021 ). After obtaining individual- and group-level modular structures, we projected them on brain surface for further comparison between different methods and different brain atlases.…”
Section: Methodsmentioning
confidence: 99%